Long-term cognitive impairments in kidney transplant recipients: impact on participation and quality of life. Issue 2 (17th February 2022) - Ziengs, Aaltje L; Buunk, Anne M; van Sonderen, Lisanne; Eisenga, Michele F; Gomes Neto, Antonio W; Annema, Coby; Vlagsma, Thialda; Navis, Gerjan J; Berger, Stefan P; Bakker, Stephan J L; Spikman, Jacoba M
ABSTRACT: Background: Cognitive impairment is often present shortly after transplantation in kidney transplant recipients (KTR). To date, it is unknown whether these impairments persist in the long term, to what extent they are associated with disease-related variables and whether they affect societal participation and quality of life (QoL) of KTR. Method: This study was part of the TransplantLines Biobank & Cohort Study in the University Medical Center Groningen. A total of 131 KTR, with a mean age of 53.6 years (SD = 13.5) transplanted ≥1 year ago ( M  = 11.2 years, range 1–41.7 years), were included and compared with 306 healthy controls (HC). KTR and HC were well matched; there were no significant differences regarding age, sex and education. All participants were assessed with neuropsychological tests measuring memory, mental speed, attention and executive functioning, and with questionnaires examining societal participation and QoL. Results: Compared with HC, KTR performed significantly worse on memory, mental speed and measures of executive functioning (all P-values <0.05). Moreover, 16% of KTR met the criteria for mild cognitive impairment (MCI), compared with 2.6% of the HC. MCI in KTR was not significantly correlated with age- and disease-related variables. Poorer cognitive functioning was significantly related to lower levels of societal participation and to lower QoL (all P-values <0.01). Conclusions: This study shows long-term cognitive impairments in KTR, which are not related to disease-related variables. Neuropsychological assessment is important to timely signal these impairments, given their serious negative impact on societal participation and QoL. Graphical Abstract: